Enhancing English learners` Willingness to Communicate through debate and philosophy inquiry discussion - Shamsudin, Mardziah; Othman, Moomala; Jahedi, Maryam; Aralas, Dalia (Canadian Center of Science and Education, 2017)
The present study investigated the impact of two instructional methods, Debate and Philosophy Inquiry (PI), in enhancing Willingness to Communicate (WTC) among two groups of English as a Second Language (ESL) learners who were randomly selected. In each group there were sixteen participants. The researchers used independent samples t-test and paired samples t-test to analyze the collected data. The data analysis using paired samples t-test showed that both methods of instruction have a significant effect on learners’ WTC. However, the learners’ WTC increased more in Debate group comparing to the Philosophy Inquiry classroom discussion group. The results indicate that Debate is more effective than Philosophy Inquiry classroom discussion in enhancing ESL learners’ WTC.